In vitro and in vivo effects of Puntius javanicus cholinesterase by copper - Sabullah M.K.; Sulaiman M.R.; Shukor M.Y.A.; Shamaan N.A.; Khalid A.; Ahmad S.A. (Parlar Scientific Publications, 2024)
Indexed by WOS/ Scopus